The role of exclusive enteral nutrition in the pre-operative optimisation of adult patients with Crohn's disease. A systematic review. (December 2021) - Gordon-Dixon, Ayeshah; Gore-Rodney, Jessica; Hampal, Rumneek; Ross, Rose; Miah, Anur; Amorim Adegboye, Amanda Rodrigues; Grimes, Caris E.
Summary: Aim: To conduct a systematic review in order to bring together the current knowledge about the use of exclusive enteral nutrition (EEN) in the pre-operative optimisation of adult patients with Crohn's disease undergoing intestinal resection. Methods: We searched Pubmed, Cochrane Library, ClinicalTrials.gov and the EU clinical trial register to identify experimental and observational studies on the effect of pre-operative EEN on nutritional and clinical outcomes of patients undergoing surgery. Methodological quality was assessed using the Downs and Black checklist. Results: Seven studies were included in the final analysis. Of these 5 were retrospective cohort studies and 2 were retrospective case-control studies. There were 4 ongoing RCTs, however they have not reported data to analyse. Overall the 7 retrospective studies, support that with EEN; body mass index (BMI) does not increase, C-reactive protein decreases (CRP), albumin usually increases and haemoglobin does not significantly change. There were fewer infectious complications in patients who had taken EEN. There was a trend towards fewer stomas but only one of the studies was powered enough to demonstrate significance. There was no significant difference in recurrence rates of Crohn's disease at 12 months in any of the studies. Quality of the studies were either medium or poor. Conclusion: The current data on the use of EEN in pre-operative optimisation is of poor quality and underpowered to demonstrate significance. Randomised controlled trials are needed to demonstrate whether or not EEN can improve outcomes and reduce stoma formation in adult patients undergoing intestinal resection.